Establishment of a degenerate primer-based multiplex qPCR method for sensitive detection of Gas-Producing Bacillus spp. in soy sauce - Huiting Huang; Jingfeng Zhang; Haoqing Zhao; Zhongsong Chen; Qian zou; Yiling Jin; Xiaobo Zeng; Lichao Zhao (Food Microbiology, 2026)

A tri-modal biosensor based on alkyne-functionalized gold nanoparticles and molecular beacon for detection of resistance-related point mutations in epidermal growth factor receptor-tyrosine kinase inhibitors - Ding Tan; Haixin Long; Ya Wang; Wenjing Lin; Yiling Huang; Haijun Chen; Yu Gao (Molecular Biology Reports, 2026)

Sustainable extraction and in situ separation of bromelain from pineapple peel using deep eutectic solvent/salt system: molecular mechanism, hydrolytic activity and stability - Yiling Liu; Qizhen Huang; Yihan Liu; Jiacong Wu; Ming Li; Yun Wang; Juan Han; Lei Wang (Food Research International, 2026)

Effects of carriers and addition modes on the physical and chemical properties of green pepper (Piper nigrum L.) powders treated by freeze-far infrared drying during storage - Xinyi Wang; Yiling Tang; Yue Huang; Hui Su; Xiaoyu Fan; Hongchen Li; Haiming Chen; Ming Zhang; Jianfei Pei; Congfa Li; Wenxue Chen; Ying Lyu (Food Chemistry, 2026)

By-Products Formation Regulated by Dissolved Organic Matter During Electrochemical Oxidation of Shale Gas Produced Water - Renmin Huang; Yiling Zhuang; Huihui Wang; Qiyue Kuang; Yong He; Zhaoji Zhang (Water, Air, & Soil Pollution, 2026)

Sophoraflavanone G disrupts human sperm function via impairing CatSper-mediated Ca2+ signaling - Meiling Yang; Ze Xu; Jiali Zhang; Nanxi Ji; Jieling Huang; Yiling Lu; Chunli Sha; Sijie Gaoliu; Xuhui Zeng; Hang Kang; Liping Chen (Reproductive Toxicology, 2026)

Synergistic catalytic elimination of NOx and chlorobenzene over Mn₅Ce₃/TiO₂/ZSM-5 catalyst: Insight into the performance and mechanism under C3H6-SCR conditions - Bo Yang; Yiling He; Yujie Lei; Qiong Huang; Mindong Chen (Journal of Environmental Chemical Engineering, 2026)

Efficient and stable membrane fouling control in MFC-MBR system facilitated by conductive membrane electrodes - Xiao Zhu; Yiling Gu; Nan Jiang; Jiaping Wu; Wenxin Chen; Suhao Feng; Ding Huang; Jianmao Yang; Manhong Huang (Journal of Water Process Engineering, 2026)

Unveiling infrastructure-induced vertical environmental inequity near elevated roads via drone-based measurements - Xing An; Yiling Zheng; Rongjia Zheng; Zengyuan Huang; Jiani Huang; Zuying Teng; Xiaoting Huang; Shouming Qi; Zirong Ma; Ruhui Cao; Zhanyong Wang (Journal of Hazardous Materials, 2026)

Migrion: a Migrasome-mediated unit for intercellular viral transmission - Yuxing Huang; Xiaojie Yan; Xing Liu; Congcong Ji; Wenmin Tian; Haohao Tang; Yong Li; Yiling Wen; Peiyao Fan; Hongli Wang; Cankun Xi; Zhongtian Li; et al. (Science Bulletin, 2026)

Integrating inventory models and satellite observations for site-level methane emission quantification from MSW landfills in China - Shuai Zhang; Xuyang Huang; Menglin Lei; YiLing Zhou; Xunchang Fei; Liangtong Zhan; Yunmin Chen; Yuzhong Zhang (Journal of Environmental Management, 2026)

A novel method for predicting fuel consumption of the LNG dual-fuel ship based on BN-GBM and feature construction - Yiling Lu; Lianzhong Huang; Yanfei Zhang; Jianlin Cao; Haoyang Zhao; Daize Li; Zhang Ruan; Kai Wang; Ranqi Ma (Ocean Engineering, 2026)

Mechanisms, treatment strategies and predictive biomarkers of drug resistance in acute myeloid leukemia - Jianjian Zhuang; Yue Li; Yingqiong Zhang; Yiling Huang; Yijia Han; Nengming Lin; Yangling Li (Mutation Research - Reviews in Mutation Research, 2026)

Enhancing agroforestry system resilience: Harnessing environmental vulnerability data to map restoration and pave the way for karst desertification control - Jie Xiao; Yiling Yang; Kangning Xiong; Shilian Jiang; Yunting Huang (Agricultural Systems, 2026)

Tannic acid: A star molecule in the construction and biomedical applications of hydrogels - Wei Zhang; Yiling Chen; Jing Huang; Ziyi Xiao; Fangjing Wang; Guihui Zhu; Xinying Liao; Yuxin Tang; Zhihao Song; Jian Sun; Yang Liu (Chemical Engineering Journal, 2025)

Functional identity drives tree species richness-induced ecosystem carbon allocation in subtropical forests - Chenyan Huang; Yiling Tian; Jie Wang; Decai Peng; Zhiqiang Shen; Chengjin Chu; Zilong Ma (Forest Ecology and Management, 2025)

General strategy for efficient persistent RTP polymer over 3 s: luminophore with a moderate θn-π angle - Danman Guo; Tong Zou; Yiling Miao; Jinzheng Chen; Zhu Chen; Xiangyu Ge; Faxu Lin; Yi Zhang; Zhenguo Chi; Zhiyong Yang; Huahua Huang (Chemical Engineering Journal, 2025)

Evaluation and optimization of a cascade PEMFC system for enhancing coalbed methane recovery considering carbon capture and carbon taxes - Aixiang Xu; Qi Yang; Lanxiang Yang; Wei Huang; Yiling Ke; Zihao Wang; Sheng Yang; Chengwei Deng (Process Safety and Environmental Protection, 2025)

Understanding how agroforestry systems biodiversity drives ecosystem services in degraded habitats - Yiling Yang; Jie Xiao; Yunting Huang; Shilian Jiang (Journal of Environmental Management, 2025)

Deep learning MRI-based radiomic models for predicting recurrence in locally advanced nasopharyngeal carcinoma after neoadjuvant chemoradiotherapy: a multi-center study - Chunmiao Hu; Congrui Xu; Jiaxin Chen; Yiling Huang; Qingcheng Meng; Zhian Lin; Xinming Huang; Li Chen (Clinical & Experimental Metastasis, 2025)

Fine particulate matter components and reproductive hormones in female adults: A 15-year longitudinal cohort study - Siyi Chen; Cui Guo; Chunquan Ou; Yiling Zheng; Yufei Liu; Jun Ma; Xingcheng Lu; Bo Huang; Ta-Chien Chan (International Journal of Hygiene and Environmental Health, 2025)

Brazilin alleviates acute lung injury via inhibition of ferroptosis through the SIRT3/GPX4 pathway - Xiaopei Yan; Li Xu; Chang Qi; Yiling Chang; Juanjuan Zhang; Ning Li; Baoyu Shi; Bo Guan; Siming Hu; Chao Huang; Hui Wang; Ying Chen; et al. (Apoptosis, 2025)

HTBPPS: A high-throughput behavioral phenotyping platform for shrimp - Wenzhi Cheng; Huimin Peng; Chuanxi Chen; Heqian Zhang; Yiming Wei; Jinqian Yang; Xiaojie Deng; Yiling Hou; Siqi Li; Tingting Huang; Yougen Chen; Chichi Liu; et al. (Aquaculture, 2025)

Human iPSC-derived mesenchymal stem cells relieve high blood pressure in spontaneously hypertensive rats via splenic nerve activated choline acetyltransferase-positive cells - Zhen Zhang; Weijun Huang; Xiaoran Zhang; Zhecun Wang; Manting Xie; Bingbing Xie; Yiling Wang; Xiaoyong Chen; Andy Peng Xiang; Qiuling Xiang (Science China Life Sciences, 2025)

Dual-CRISPR/Cas12a-assisted RT-RAA visualization system for rapid on-site detection of nervous necrosis virus (NNV) - Jie Gao; Siyou Huang; Jing Jiang; Qijin Miao; Rui Zheng; Yiling Kang; Wanting Tang; Hongliang Zuo; Jianguo He; Junfeng Xie (Analytica Chimica Acta, 2025)

An improved soil moisture retrieval method considering azimuth angle changes for spaceborne GNSS-R - Yiling Ye; Lilong Liu; Fade Chen; Liangke Huang (Advances in Space Research, 2025)

Impact of dietary protein and lipid levels and growth rates on the intestinal microbiota of kuruma shrimp (Penaeus japonicus) - Chuanxi Chen; Chunxiang Ai; Wenzhi Cheng; Huiyang Huang; Guangjie Fang; Yiling Hou; Xiaojie Deng; Siqi Li; Tingting Huang; Yougen Chen; Peng Xu; Yong Mao (Aquaculture International, 2025)

Two cytokine receptor family B (CRFB) members in orange-spotted grouper Epinephelus coioides, EcCRFB3 and EcCRFB4, negatively regulate interferon immune responses to assist nervous necrosis virus replication - Siyou Huang; Yiling Kang; Rui Zheng; Linwei Yang; Jie Gao; Wanting Tang; Jing Jiang; Jianguo He; Junfeng Xie (Fish & Shellfish Immunology, 2024)

Rapid fluorescent nucleic acid sensing with ultra-thin gold nanosheets - Peiyin Li; Huiyang Zhang; Zhenyu Yang; Yiling Li; Manli Huang; Lingzhi Yang; Xueji Zhang (Analytica Chimica Acta, 2024)

LDH nanocrystal@amorphousness core–shell structure derived from LDH → LDO transformation: Synergistically enhanced energy stored for LIBs anode - Kai Yang; Yiling Huang; Peixing Wang; Yixuan Tang; Yiwen Zhu; Xiaoxue Zhu; Yan Xu; Wei Jiang; Limei Pan; Qian Li; Haijiao Xie; Jian Yang (Chemical Engineering Journal, 2024)

Orange-spotted grouper IFNh response to NNV or MSRV and its potential antiviral activities - Siyou Huang; Rui Zheng; Yiling Kang; Linwei Yang; Jie Gao; Qingqing Liu; Shaoping Weng; Jianguo He; Junfeng Xie (Fish & Shellfish Immunology, 2024)

Prediction of Total Phosphorus Based on Distance Correlation and Machine Learning Methods—a Case Study of Dongjiang River, China - Yongkai Huang; Yiling Chen (Water, Air, & Soil Pollution, 2024)

DNA hypomethylation-associated transcriptional rewiring enables resistance to heavy metal mercury (Hg) stress in rice - Weixuan Cong; Ning Li; Yiling Miao; Yuxi Huang; Wenhao Zhao; Ying Kang; Bingqi Zhang; Jinbin Wang; Jiayu Zhang; Yinhe Lv; Jiamo Li; Jian Zhang; et al. (Journal of Hazardous Materials, 2024)

Chiral Au nanostars for SERS sensing of enantiomers discrimination, multibacteria recognition and photothermal antibacterial application - Xueqin Huang; Qiuxia Chen; Yiling Ma; Chan Huang; Weixia Zhi; Jiahao Li; Runmin Zeng; Jiang Pi; Jun-fa Xu; Jun Xu; Wanyong Yang; Jianglin Zhang; et al. (Chemical Engineering Journal, 2024)

Identification of lead-binding proteins as carriers and potential molecular targets associated with systolic blood pressure - Qiying Nong; Baowei Chen; Yongshun Huang; Yiling Li; Yuanyuan Wang; Lihong Liu; Bin He; Tiangang Luan; Ligang Hu; Guibin Jiang (Chemosphere, 2023)

Effects of dietary adenosine and adenosine 5′-monophosphate supplementation on carcass characteristics, meat quality, and lipid metabolism in adipose tissues of finishing pigs - Sujuan Rao; Zhijuan Cui; Longmiao Zhang; Shuo Ma; Shuangbo Huang; Li Feng; Yiling Chen; Jinxi Luo; Jinfeng Li; Shiyu Qian; Hanting Liu; Yanzhi Liu; et al. (Meat Science, 2023)

A smartphone-assisted “all-in-one” paper chip for one-pot noninvasive detection of salivary glucose level - Qian Lin; Jiaqi Huang; Yiling Zhang; Miaomiao Chen; Yuzhi Xu; Xiaoyong Zou; Si-Yang Liu; Zong Dai (Chemical Engineering Journal, 2023)

Experimental Investigation of the Mechanical Properties and Energy Evolution of Layered Phyllite Under Uniaxial Multilevel Cyclic Loading - Jiabing Zhang; Ronghuan Du; Yiling Chen; Zhen Huang (Rock Mechanics and Rock Engineering, 2023)

Cation-mediated Pt site-selective trimetallic nanostructures for high-performance electrocatalysis - Jingxian Zhang; Haoyang Huang; Wenbo Wang; Shi Zeng; Xu Zhang; Yiling Bai; Guangjin Zhang (Chemical Engineering Journal, 2023)

No tillage outperforms conventional tillage under arid conditions and following fertilization - Stavros D. Veresoglou; Junjiang Chen; Xuheng Du; Qi Fu; QingLiu Geng; Chenyan Huang; Xilin Huang; Nan Hu; Yiming Hun; Guolin C. Li; Zhiman Lin; Zhiyu Ma; et al. (Soil Ecology Letters, 2023)

Exploration of molecular mechanism of intraspecific cross-incompatibility in sweetpotato by transcriptome and metabolome analysis - Yiling Yang; Xiongjian Zhang; Hongda Zou; Jingyi Chen; Zhangying Wang; Zhongxia Luo; Zhufang Yao; Boping Fang; Lifei Huang (Plant Molecular Biology, 2022)
Cross-incompatibility, frequently happening in intraspecific varieties, has seriously restricted sweetpotato breeding. However, the mechanism of sweetpotato intraspecific cross-incompatibility (ICI) remains largely unexplored, especially for molecular mechanism. Treatment by inducible reagent developed by our lab provides a method to generate material for mechanism study, which could promote incompatible pollen germination and tube growth in the ICI group. Based on the differential phenotypes between treated and untreated samples, transcriptome and metabolome were employed to explore the molecular mechanism of sweetpotato ICI in this study, taking varieties ‘Guangshu 146’ and ‘Shangshu 19’, a typical incompatible combination, as materials. The results from transcriptome analysis showed oxidation–reduction, cell wall metabolism, plant–pathogen interaction, and plant hormone signal transduction were the essential pathways for sweetpotato ICI regulation. The differentially expressed genes (DEGs) enriched in these pathways were the important candidate genes to response ICI. Metabolome analysis showed that multiple differential metabolites (DMs) involved oxidation–reduction were identified. The most significant DM identified in comparison between compatible and incompatible samples was vitexin-2-O-glucoside, a flavonoid metabolite. Corresponding to it, cytochrome P450s were the most DEGs identified in oxidation–reduction, which were implicated in flavonoid biosynthesis. It further suggested oxidation–reduction play an important role in sweetpotato ICI regulation. To validate function of oxidation–reduction, reactive oxygen species (ROS) was detected in compatible and incompatible samples. The green fluorescence was observed in incompatible but not in compatible samples. It indicated ROS regulated by oxidation–reduction is important pathway to response sweetpotato ICI. The results in this study would provide valuable insights into molecular mechanisms for sweetpotato ICI.

Temperature-sensitive morbidity indicator: consequence from the increased ambulance dispatches associated with heat and cold exposure - Qingchuan Wang; Yiling He; Shakoor Hajat; Jian Cheng; Zhiwei Xu; Wenbiao Hu; Wenjun Ma; Cunrui Huang (International Journal of Biometeorology, 2021)

Pgant4 and Tango1 Mediate Anoxia and Reoxygenation Injury - Qingqing Du; Nastasia K. H. Lim; Yiling Xia; Wangchao Xu; Qichao Zhang; Liyao Zhang; Fude Huang; Wenan Wang (Neuroscience Bulletin, 2020)

An Efficient and Reliable Assay for Investigating the Effects of Hypoxia/Anoxia on Drosophila - Yiling Xia; Wangchao Xu; Shiquan Meng; Nastasia K. H. Lim; Wenan Wang; Fu-De Huang (Neuroscience Bulletin, 2018)

Molecular characterization and association analysis of porcine PANE1 gene - Honggang Huang; Hong Deng; Yiling Yang; Zhonglin Tang; Shulin Yang; Yulian Mu; Wentao Cui; Jing Yuan; Zhenfang Wu; Kui Li (Molecular Biology Reports, 2010)